Compassion: Research, applications and multi-cultural considerations - Matos, Marcela (2021)
Compassion is an ancient concept but novel hot topic across the social sciences, from psychology, to sociology, to health, to communication and media, to politics and beyond. Burgeoning research has demonstrated the benefits of compassion for mental health and emotion regulation (e.g., MacBeth & Gumley, 2012; Matos et al., 2022), physiological health (e.g., Fredrickson et al., 2013; Kim et al., 2020; Klimecki et al., 2014), and interpersonal and social relationships (e.g., Crocker & Canevello, 2012; Yarnell & Neff, 2013). In particular, self-compassion has been shown to be a protective factor, increasing resilience to common mental health issues (e.g., shame, self-criticism; MacBeth & Gumley, 2012; Muris & Petrocchi, 2017) and promoting wellbeing (Zessin et al., 2015). In addition to compassion offering wellbeing benefits, compassion and self-compassion can also be cultivated and enhanced through interventions, in diverse populations and contexts, where they have been shown to promote well-being and to diminish mental health difficulties (e.g., depression, anxiety, stress, shame, self-criticism) (e.g., Craig et al., 2020; Ferrari et al., 2019; Kirby et al., 2017). Given the global challenges facing our world and the need for collective action, and inspired by the notion in evolutionary science that a conscious evolution toward a more compassionate world is possible (see Wilson, 2020), this special issue of the journal Psychologica presents research, applications and multi-cultural considerations related to compassion. In this special issue, several researchers and clinicians, including prominent names in the field and history of compassion, such as Prof. Paul Gilbert, made valuable contributions to expand the science of compassion and disseminate this knowledge into community, educational, clinical and public health settings. These studies are focused on different cultures (Portuguese, Australian, Singaporean), populations (clinical and nonclinical), age groups (adolescents and adults), clinical conditions (Borderline Personality Disorder, Social Anxiety Disorder Hoarding Disorder), and applications (compassion-based programs for adolescents and adults, for distinct clinical conditions and with different formats). Let us give you a short-guided tour through the headlines of this special issue. (...)